R-Spondins and Wnt Signalling Pathway: A Periodontal Perspective - NK Savithri; S Sangeetha; Jesintha Mary; PM Gayathri (Journal of Clinical and Diagnostic Research, 2023)
Periodontitis is a multifactorial chronic condition associated with the formation of a dysbiotic biofilm, leading to inflammation that can modulate cell signaling. R-spondins (Rspos) are cysteine-rich secreted glycoproteins which control a variety of functions which are essential for embryonic development and tissue homeostasis. Numerous studies have explained about their pivotal role in critical developmental regulators, the most important finding being Rspos synergise Wingless/Integration (Wnt) signaling. Novel receptors for Rspos, the Leucine-rich repeat containing G protein-coupled (LGR) receptors, proposed that Rspos potentiate canonical Wnt signaling via these receptors. Here, authors discussed about the Wnt signaling and outlined the biological role of Rspos in tissue development and homeostasis and explore the possibility that Rspos may be used as therapeutic targets. Wnt5a is important for promoting periodontal ligament remodeling and impairing regenerative responses modulated by the Wnt/β-catenin pathway, for alveolar bone formation.